Biomechanical evaluation of the unilateral crossbite on the asymmetrical development of the craniofacial complex. A mechano-morphological approach. (April 2022) - Ortún-Terrazas, Javier; Fagan, Michael J.; Cegoñino, José; Illipronti-Filho, Edson; del Palomar, Amaya Pérez
Highlights: Computational models simulate the occlusal imbalance with relative errors below 6%. Centric occlusion simulations shows the functional imbalance of crossbite patients. Crossbite patients present asymmetrical strains and shifts in jaw and maxilla. Facial asymmetry and the unilateral crossbite relationship is proved. Computational analyses demonstrate functional matrix hypothesis principles. Abstract: Background and Objective: The occlusion effect on the craniofacial development is a controversial topic that has attracted the interest of many researchers but that remains unclear, mainly due to the difficulties on measure its mechanical response experimentally. This mechano-morphological relationship of the craniofacial growth is often explained by the periosteal and capsular matrices of the functional matrix hypothesis (FMH); however, its outcomes have not been analytically demonstrated yet. This computational study aims, therefore, to analytically demonstrate the mechano-morphological relationship in the craniofacial development of children with unilateral crossbite (UXB) using the finite element (FE) method. Methods: The craniofacial complex asymmetry of ten children, five of whom exhibit UXB, was 3D-analysed and compared with the biomechanical response computed from a FE analysis of each patient's occlusion. Due to the complexity of the geometry and the multitude of contacts involved, the inherent limitations of the model were evaluated by comparing computed occlusal patterns with those recorded by an occlusal analysis on 3D printed copies. Results: Comparison's outcomes proved the reliability of our models with just a deviation error below 6% between both approaches. Out of validation process, computational results showed that the significant elongation of mandibular branch in the contralateral side could be related to the mandibular shift and increase of thickness on the crossed side, and particularly of the posterior region. These morphological changes could be associated with periodontal overpressure (>4.7 kPa) and mandibular over deformation (0.002 ε) in that side, in agreement with the periosteal matrix's principles. Furthermore, the maxilla's transversal narrowing and the elevation of the maxillary and zygomatic regions on the crossed side were statistically demonstrated and seem to be related with their respective micro displacements at occlusion, as accounted by their specific capsule matrices. Our results were consistent with those reported clinically and demonstrated analytically the mechano-morphological relationship of children's craniofacial development based on the FMH's functional matrices. Conclusions: This study is a first step in the understanding of the occlusion's effect on the craniofacial development by computational methods. Our approach could help future engineers, researchers and clinicians to understand better the aetiology of some dental malocclusions and functional disorders improve the diagnosis or even predict the craniofacial development. Graphical abstract: Image, graphical abstract